Novel humanized CD19-CAR-T (Now talicabtagene autoleucel, Tali-cel™) cells in relapsed/ refractory pediatric B-acute lymphoblastic leukemia- an open-label single-arm phase-I/Ib study - Gaurav Narula; Swaminathan Keerthivasagam; Hasmukh Jain; Sachin Punatar; Akanksha Chichra; Chetan Dhamne; Prashant Tembhare; Papagudi Ganesan Subramanian; Nikhil Patkar; Minal Poojary; Anant Gokarn; Sumeet Mirgh; et al. (Blood Cancer Journal)
Abstract Chimeric Antigen Receptor-T (CAR-T) cell therapy is effective for relapsed/refractory B-acute lymphoblastic leukemia (r/r B-ALL) but is not universally available. We developed a novel humanized CD19-directed CAR-T (HCAR19) approved for Phase 1/1b/2 trials. Patients aged 3–25 years were enrolled with r/r B-ALL and ineligible for allogeneic stem cell transplant. Lymphodepletion utilized standard-dose fludarabine and cyclophosphamide. A 3 + 3 design testing 3 dose-ranges was used to determine Phase-2 Dose (P2D): Dose-A, 1 × 106 HCAR19 cells/kg, Dose-B, 3–5 × 106/kg, and Dose-C, 10–15 × 106/kg. Primary endpoint was overall response rate (ORR) at day-30 on bone-marrow flow-cytometry. From May-2021 to September-2023 12 patients [median age-14 (range: 5–24) years] were enrolled with median bone marrow blasts 19.5% at screening. Cytokine release syndrome occurred in 10 (83%) patients, predominantly Grades 1–2, and Grade-2 immune-cell associated neurotoxicity (ICANS) in 1. All patients had Grade-3 cytopenia. ORR was 91.7% (11/12), complete response (CR) in 8 (66.7%) and partial response in 3 (25%). Seven of 8 CRs were at Dose-levels B and C, all of which were sustained till 12 months follow-up. Patients who received dose levels below 3 × 106/kg, or did not achieve CR, had early loss of response or rapid progression. HCAR19 demonstrated safety, manageable toxicity, and durable remissions. and P2D was determined as 5–10 × 106 HCAR19-cells/kg. Clinical trial registration The study is registered in the Clinical Trials Registry- India (CTRI/2021/05/033348 and CTRI/2023/03/050689).